1994
DOI: 10.2323/jgam.40.35
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress conditioning for induction of acquired osmotolerance in Escherichia coli.

Abstract: Escherichia coli cells exhibited osmotolerance and grew well even in hyperosmotic medium containing 1.2 M NaCI (or 2.0 M sorbitol) if they had been previously exposed to moderate osmotic stress for a short time (30min). Untreated cells showed repressed growth. This acquirement of osmotolerance against hyperosmolarity was dependent on the concentration of the osmoticum in the osmotic stress conditioning. The most effective conditioning occurred when almost the same moderate osmolarity of electrolytes (about 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As a macronutrient for E. coli growth, potassium is involved in a number of fundamental biological processes including maintaining the osmotic balance of cells 25. NaOH is a widely available low‐price commodity chemical, and E. coli has been reported to grow in media containing high concentrations of sodium 26. Na 2 CO 3 and K 2 CO 3 were used to investigate if additional carbonate would increase the carbon flux to succinate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a macronutrient for E. coli growth, potassium is involved in a number of fundamental biological processes including maintaining the osmotic balance of cells 25. NaOH is a widely available low‐price commodity chemical, and E. coli has been reported to grow in media containing high concentrations of sodium 26. Na 2 CO 3 and K 2 CO 3 were used to investigate if additional carbonate would increase the carbon flux to succinate.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is further substantiated by the results from the fermentations supplemented with glycine betaine (Table 2). There are numerous studies and reviews on osmotic stress and osmotolerance in bacteria 26, 29–31. E. coli subjected to osmotic stress respond by accumulating compatible solutes, such as glycine betaine, proline, and trehalose 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the stresses are capable of inducing a response that may be specific or global, offering cross protection to different challenging stresses. Conditions such as pH (13), osmolarity (14) and heat (15,16) induce different stress-response pathways. The essential signal required to induce a particular pathway and the threshold required for this induction are currently receiving attention, but they remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported (12,13) that the osmotolerance of E. coli cells against hyper-osmolarity could be acquired easily by prior exposure to a moderate salinity stress for a short time (about 30 min). However, it is not at all clear why the moderate salinity stress was effective on the induction of acquired osmotolerance in E. codi.…”
mentioning
confidence: 99%
“…coli ATCC-9637 was aerobically cultured as described by Ishida et al (12) in a nutrient broth (pH 7.0) containing 10 g of yeast extract (Dried yeast extract D-3, Nihonseiyaku KK, Tokyo, Japan), 10 g of polypeptone (Nihonseiyaku KK), and 2 g of NaCI in 1,000 ml of distilled water. After 12 h of culture, cells were collected by centrifugation (10,000 X g for 5 min, 4°C), washed twice with distilled water unless otherwise stated, and stored at 4°C until used.…”
mentioning
confidence: 99%